Trend of mosquito (Diptera: Culicidae) monthly distribution in Sanandaj County of Iran - Bahadin Salavati; AMIR HOSSEIN ZAHIRNIA; Hassan Nasirian; SHAHYAD AZARI-HAMIDIAN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Salavati B, Zahirnia AH, Nasirian H, Hamidian SA. 2021. Trend of mosquito (Diptera: Culicidae) monthly distribution in Sanandaj County of Iran. Biodiversitas 22: 4705-4715. Mosquitoes are the most significant arthropods of medical importance due to their burden of transmitting pathogens and parasites. The present study was designed to investigate the distribution of mosquitos (Diptera: Culicidae) in Sanandaj County in 2018. Sanandaj County was divided into four areas in rural and urban areas, including north, south, east, and west. Four rural and urban areas were randomly selected from four geographical directions. A sampling of larval and adult mosquitoes was performed using standard methods. The dipping technique was used to collect the mosquito larvae. A sampling of adult mosquitoes was performed during feeding on humans and animal baits and resting in the natural indoors, outdoors, and artificial areas. Light traps were also used to collect adult mosquitoes. The larval and adult specimens were identified using the morphology-based key. In total, nine mosquito species, including Anopheles maculipennis s.l., Anopheles superpictus s.l., Culiseta longiareolata, Culiseta subochrea, Culex hortensis, Culex mimeticus, Culex modestus, Culex pipiens, and Culex theileri were inhabited in Sanandaj County. The larval and adult mosquito species trend remains constant for at least 6 months of a year, from May to October. One-way ANOVA didn't reveal a significant difference between mosquito breeding places' habitats and water types, mosquito localities and life stages, monthly mosquito distribution, and adult mosquito resting places. The frequency trends of larval and adult mosquito species remain constant at least for 6 months of a year. It needs to be ready for timely mosquito control measures.